Reproductive and sexual health promotion in a sensitive socio-cultural environment developing a module for the grassroots - Hashima-e-Nasreen; Cash, Kathy; Chowdhury, Mushtaque; Bhuiya, Abbas; Ahmed, Syed Masud (BRAC Research and Evaluation Division (RED), 2019)
The general population of Bangladesh is in poor health, has little access to health facilities, has increasing incidence of STDs and is in close proximity to countries with high rates of HIV/AIDS. Up to date little has been done to educate rural Bangladesh citizens about STDs including HIV/AIDS, RTls and other sexual and reproductive health problems. In 1997 a sexual and reproductive health project began in a rural community under the collaborative research model of two organizations, the International Centre for Diarrheal Disease Research (ICDDR,B) and the Bangladesh Rural Advancement Committee (BRAC), an indigenous non-governmental organization which pursues integrated rural development strategies. The goal of this project was to improve the sexual and reproductive health of rural women, men and youth in Bangladesh. The target population was a representative sample of the rural poor. Initial qualitative in-depth interviews with 65 different women, men, boys and girls revealed significant sexual health problems and experiences and little knowledge about treatment and prevention. Data from these initial interviews was transformed into a series of flip-charts which contained both sex education information and picture stories that mirrored risk behavior. Because of the sensitive nature of the topics, only those who had perceived legitimacy to talk about sexual health were identified and trained. Sixty eight health providers and 1890 community people were trained. Qualitative evaluations of health providers revealed significant changes in their knowledge and bt4iiefs about sexual health and disease. Health providers integrated the program into their ongoing work. Furthermore, they reported improvements in their selfconfidence, btJsiness, personal interactions with their family members and with their clients due to this program. In conclusion, this program demonstrated that a gender-sensitive sexual and reproductive health initiative could be a positive force for change in a rural Bangladesh setting.